The Role of Muhammadiyah Politics in Advocating for Reform of The Legislative Electoral System (DPR/DPRD) in Post-New Order Indonesia (1999–2024) - Ahmad Islamy Jamil; Aditya Perdana (International Journal Labs, 2025)
This study examines the political role of Muhammadiyah as a civil society organization (CSO) in advocating for reform of the legislative electoral system (DPR/DPRD) in post-New Order Indonesia (1999–2024). Using the theory of the function of civil society from Wolfgang Merkel (1999) and the theory of public policy advocacy from Start and Hovland (2004), this study explores the reasons why Muhammadiyah persistently encourages changes in the open proportional system (OLPR), the internal actors involved, and the strategies used. The method in this study uses a qualitative approach with a case study design that relies on primary data sources of interview results supported by related secondary data. The findings show that Muhammadiyah carries out the function of supervision of the state and articulation of social interests, criticizing the OLPR for triggering money politics, polarization, and lack of meritocracy. Muhammadiyah proposed a closed proportional system (CLPR) or Moderate List Proportional Representation (MLPR) through a scientific study by the Institute of Wisdom and Public Policy (LHKP). Advocacy strategies include collaborative advising, lobbying, and public promotion, although hampered by political party resistance and internal dynamics. This research contributes to the study of civil society and elections in transitional democracies, highlighting the importance of reforming the electoral system that is fair and democratic..